Integrasi Principal Component Analysis dan Logistic Regression untuk Analisis Sentimen Kepuasan Pelanggan Berdasarkan Ulasan Online - Tsalsabila Jilhan Haura; Rini Sovia; Gunadi Widi Nurcahyo (Bulletin of Computer Science Research, 2026)
Customer reviews on digital platforms are an important source of information for evaluating service quality and customer satisfaction levels. However, the unstructured nature of review data and its high feature dimensionality pose challenges in the sentiment analysis process. This study aims to develop a customer sentiment analysis model by integrating Principal Component Analysis (PCA) and Logistic Regression. The data used are 679 Indonesian-language reviews obtained through web scraping techniques from Google Reviews at ten d'Besto EBM branches in Padang City. The research stages include text preprocessing, TF-IDF weighting, dimensionality reduction using PCA, and sentiment classification using Logistic Regression. The results show that PCA is able to reduce data complexity by producing two principal components that explain 85.7% of the total data variance. The Logistic Regression model built on the features resulting from PCA reduction achieved an accuracy of 82%, demonstrating the model's ability to effectively classify positive and negative sentiments. In addition to improving computational efficiency, the use of PCA also helps reduce feature redundancy in high-dimensional text data. The contribution of this research is to produce a simpler and more efficient sentiment analysis approach to process customer reviews and provide data-based information that can be used to support service quality evaluation and decision-making in the culinary industry.